Between Expiatory Religious Processions and Individual Escapes: Responses to Bubonic Plague Epidemics in the Historiae of Gregory of Tours and Paul the Deacon - Demarchi, Nicole (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2022)
The aim of this article is to explore individual and collective responses to plague outbreaks in Italy and Merovingian Gaul between the mid-sixth and -seventh centuries through the narrations of two Latin Christian authors: Gregory of Tours (538/539–594) and Paul the Deacon (c.720s–c.799). Firstly, it focuses on Gregory’s plague accounts, stressing the contrast he offers between bishops who were able to manage plague epidemics though individual and/or collective religious practices and those whose efforts proved inadequate. Secondly, the article examines Paul’s plague narrative, highlighting the difficulties posed by his ambiguous vocabulary and his personal and theological concerns. Finally, it analyzes the Roman plague outbreak of 590, which is recounted by both Gregory and Paul. The article attempts to understand how the two authors perceived and evaluated plague responses within different cultural and political contexts and what the differences and similarities were between their reports on the 590 Roman plague.